Angiotensin converting enzyme activity and evolution of pulmonary vascular disease in rats with monocrotaline pulmonary hypertension. Issue 2 (February 1982) - Kay, J M; Keane, P M; Suyama, K L; Gauthier, D
Abstract : We have investigated the role of angiotensin converting enzyme (ACE) in the development of pulmonary hypertension, right ventricular hypertrophy, and pulmonary vascular disease in rats given a single subcutaneous injection of the pyrrolizidine alkaloid monocrotaline. Thirty-six young female Wistar rats were divided into a test group of 27 animals and a control group of nine animals. Each test rat was given a single subcutaneous injection of monocrotaline (60 mg/kg body weight). On the first, third, fifth, seventh, tenth, twelfth, fourteenth, seventeenth, and twenty-second days after the injection of monocrotaline the mean right ventricular systolic blood pressure was measured in one control and three test rats. The animals were then killed and we measured the specific activity of ACE in serum and lung homogenate. We also evaluated muscularisation of pulmonary arterioles, medial hypertrophy of muscular pulmonary arteries, and right ventricular hypertrophy. The sequence of changes was as follows: muscularisation of pulmonary arterioles and medial hypertrophy of muscular pulmonary arteries were apparent seven days after administration of monocrotaline; pulmonary hypertension and reduced lung ACE activity occurred after 10 days; right ventricular hypertrophy was detected after 12 days. Serum ACE activity was unchanged. It is concluded that the reduction in lung ACE activity is a result rather than a cause of the pulmonary hypertension. This reduction in lung ACE activity may be a protective mechanism designed to limit the elevation of the pulmonary arterial pressure.